Analisis Perbandingan Metode Desain Pelat Beton Konvensional Terhadap Slab Steel Deck Komposit - Muhammad Sofyan; Abdul Rokhman; Ade Okvianti Irlan (Sekolah Tinggi Teknik - PLN, 2019)
Like other structures, floor slabs also develop over time. The shorter time demands of work with lower costs are one reason for the development of structures in the construction of houses. Floor plate work can be done with two methods The conventional floor tiles of many multilevel buildings use reinforcement to bear the positive moment. While for carrying positive reinforcement, other materials can be used, namely Steel Deck Slab which will cause a composite action on the plate. The research has been conducted on the design of composite steel decks in Indonesia. The purpose of this study was to find out and compare the Capacity Efficiency of the conventional plate design and the composite Composite Steel Deck Slab with variations in plate thickness 8, 10 and 12 cm and compare the nominal moment of the cross section. By comparing these two types of plates the design engineer can determine the optimal dimensions.